The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1034/j.1600-0447.2000.101005360.x
|View full text |Cite
|
Sign up to set email alerts
|

European Consultation–LiaisonPsychiatric Services:the ECLW Collaborative Study

Abstract: Objective:To describe the patterns of organization of consultationliaison (C-L) services in 11 European countries in relation to hospital characteristics and national approaches to C-L psychiatry. Method: Cross-sectional survey. Results: Services can best be described in terms of their size and seniority of their staff and whether or not they are multidisciplinary. Singlediscipline services are based upon the standard medical consultant model, whereas those with multidisciplinary teams work in a way that is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The relatively high prevalence of alcohol and substance abuse disorders as reported in both the GH (51)(52)(53)(54), and in CLP settings (55)(56)(57), highlight the fact that, at least in Italy, consultations for addictive disorders are still probably carried out by specific programs other than CL services. Anxiety disorders, compared with Study 1, were found to be significantly less prevalent, although with a similar rate found in other studies carried out in other countries (50,58). This is consistent with a significant increase of antidepressants prescriptions in Italy during the last decades (59), as shown by the higher rates of patients being already in antidepressant treatment at the time of consultation.…”
Section: Discussionsupporting
confidence: 88%
“…The relatively high prevalence of alcohol and substance abuse disorders as reported in both the GH (51)(52)(53)(54), and in CLP settings (55)(56)(57), highlight the fact that, at least in Italy, consultations for addictive disorders are still probably carried out by specific programs other than CL services. Anxiety disorders, compared with Study 1, were found to be significantly less prevalent, although with a similar rate found in other studies carried out in other countries (50,58). This is consistent with a significant increase of antidepressants prescriptions in Italy during the last decades (59), as shown by the higher rates of patients being already in antidepressant treatment at the time of consultation.…”
Section: Discussionsupporting
confidence: 88%
“…Clinical procedures for psychiatric consultations follow indications from international evidence adapted to local context features. An electronic database was adopted by the CLPS for audit purposes after the involvement of the service in the research studies on CLP promoted in Europe by the ECLW in the late ‘90s [ 25 , 26 , 27 ]. For privacy reasons, it was decided to work on the aggregate data provided by this electronic database (through the request of appropriate “queries”).…”
Section: Methodsmentioning
confidence: 99%
“…As the presence of multiple disciplines is required for the provision of differentiated services, apparently many C-L services are sufficiently equipped to provide such a differentiated range of services. The interaction between these factors is further elaborated in a separate article [12].…”
Section: Availability Of Psychosocial Services and Organization Of C-mentioning
confidence: 99%